Geographical variation in HIV testing in South Africa: Evidence from the 2017 national household HIV survey - Sean Jooste; Musawenkosi Mabaso; Myra Taylor; Alicia North; Yolande Shean; Leickness C. Simbayi; Tarylee Reddy; Leonard Mwandingi; Tenielle Schmidt; Portia Nevhungoni; Samuel Manda; Khangelani Zuma (AOSIS, 2021)
Background: Identification of the geographical areas with low uptake of HIV testing could assist in spatial targeting of interventions to improve the uptake of HIV testing. Objectives: The objective of this research study was to map the uptake of HIV testing at the district level in South Africa. Method: The secondary analysis used data from the Human Sciences Research Council's 2017 National HIV Prevalence, Incidence, Behaviour and Communication Survey, where data were collected using a multistage stratified random cluster sampling approach. Descriptive spatial methods were used to assess disparities in the proportion of those ever tested for HIV at the district level in South Africa. Results: The districts with the highest overall coverage of people ever having tested for HIV ( 85%) include West Rand in Gauteng, Lejweleputswa and Thabo Mofutsanyane in Free State, and Ngaka Modiri Molema in North-West. These provinces also had the least variation in HIV testing coverage between their districts. Districts in KwaZulu-Natal had the widest variation in coverage of HIV testing. The districts with the lowest uptake of HIV testing were uMkhanyakude (54.7%) and Ugu (61.4%) in KwaZulu-Natal and Vhembe (61.0%) in Limpopo. Most districts had a higher uptake of HIV testing amongst female than male participants. Conclusion: The uptake of HIV testing across various districts in South Africa seems to be unequal. Intervention programmes must improve the overall uptake of HIV testing, especially in uMkhanyakude and Ugu in KwaZulu-Natal and Vhembe in Limpopo. Interventions must also focus on enhancing uptake of HIV testing amongst male participants in most districts. Strategies that would improve the uptake of HIV testing include HIV self-testing and community HIV testing, specifically home-based testing.